A Review on Principles and Applications of Scanning Thermal Microscopy (SThM). (2nd September 2019) - Zhang, Yun; Zhu, Wenkai; Hui, Fei; Lanza, Mario; Borca‐Tasciuc, Theodorian; Muñoz Rojo, Miguel
Abstract: As the size of materials, particles, and devices shrinks to nanometer, atomic, or even quantum scale, it is more challenging to characterize their thermal properties reliably. Scanning thermal microscopy (SThM) is an emerging method to obtain local thermal information by controlling and monitoring probe–sample thermal exchange processes. In this review, key experimental and theoretical components of the SThM system are discussed, including thermal probes and experimental methods, heat transfer mechanisms, calibration strategies, thermal exchange resistance, and effective heat transfer coefficients. Additionally, recent applications of SThM to novel materials and devices are reviewed, with emphasis on thermoelectric, biological, phase change, and 2D materials. Abstract : This review discusses the progress of key experimental and theoretical components of scanning thermal microscopy including thermal probes, experimental methods, heat transfer mechanisms, and calibration strategies and highlights the recent applications to novel materials and devices, with emphasis on thermoelectric, biological, phase change, and 2D materials.